New photoplethysmogram indicators for improving cuffless and continuous blood pressure estimation accuracy - Lin, Wan-Hua; Wang, Hui; Samuel, Oluwarotimi Williams; Liu, Gengxing; Huang, Zhen; Li, Guanglin (Physiological measurement, 2018)
Objective: The accuracy of cuffless and continuous blood pressure (BP) estimation has been improved, but it is still unsatisfactory for clinical uses. This study was designed to further increase BP estimation accuracy. Approach: In this study, a number of new indicators were extracted from photoplethysmogram (PPG) recordings and a linear regression method was used to construct BP estimation models based on the PPG indicators and pulse transit time (PTT). The performance of the BP estimation models was evaluated by the PPG recordings from 22 subjects when they performed mental arithmetic stress and Valsalva's manoeuvre tasks that could induce BP fluctuations. Main results: Our results showed that the best PPG-based BP estimation model could achieve a decrease of 0.31  ±  0.08 mmHg in systolic BP (SBP) and 0.33  ±  0.01 mmHg in diastolic BP (DBP) on estimation errors of grand absolute mean (GAM) and standard deviation (GSD) in comparison to the previously reported PPG-based methods. The best estimation model based on the combination of PPG and PPT could achieve a decrease (GAM & GSD) of 0.81  ±  0.95 mmHg in SBP and 0.75  ±  0.54 mmHg in DBP in comparison to the PPT-based methods. Significance: The findings suggest that the newly proposed PPG indicators would be promising for improving the accuracy of continuous and cuffless BP estimation.